Time dependence of morphological and optical properties of DC sputtering grown copper oxide thin film - Sulaiman, Rosmaizatul Akma (2014)
Copper oxide thin films with five different deposition times (30 min, 60 min, 90 min, 120 min and 150 min) had been successfully growth by dc sputtering technique. The thickness of copper oxide thin film was measured by using ellipsometer. The optical properties of copper oxide thin films were characterized by UV-Vis-NIR spectrometer and Photoluminescence spectrometer while the morphology images were determined by Atomic Force Microscopy (AFM). The copper oxide thin film thicknesses were found around 11.6 nm, 122.1 nm, 129.7 nm, 142.4 nm and 144.2 nm with respect to the five different depositions time at 30 min time interval. The absorption and transmission spectra obtained from UV-Vis-NIR spectroscopy revealed five absorption edges of copper oxide thin film in the ultraviolet region. The optical absorption intensity was increased with increase the thickness while the transmission intensity was decreased with increase the thickness. The transmission intensity was increased to 90% for copper oxide with deposition time 30 min, 60 min, 90 min, and 120 min while the transmission intensity of copper oxide with deposition time 150 min was increased up to 75%. Based on the absorption coefficient measurements, the optical band gap energy have been determined by Tauc plot relation around Eg= 4.63 eV to 4.18 eV for 30 min to 150 min of deposition time. The photoluminescence spectra of copper oxide thin film was found in violet region (400 nm and 402 nm) for copper oxide thin film with deposition time 30 min and 60 min while the blue region (435 nm) was found for copper oxide thin film at deposition time 90 min, 120 min and 150 min. The root mean square roughness (RMS) was confirmed that the surface roughness of copper oxide thin film was increased with increase the deposition time and compatible with the images shown by Atomic Force Microscopy (AFM).